Voting pattern and Nigeria’s 2019 general election - Moruf, Adebiyi Oluwashina (Humanities, Arts and Social Sciences Studies, 2021)
Since Nigeria returned to democratic governance in 1999, elections have been held regularly. The outcome of the 2019 general elections, however, brought about unexpected victories and losses for both candidates and political parties. Thus, the question is: what informed the pattern of voting in the 2019 general elections in Nigeria? It is on this basis that this article examined the voting pattern of the 2019 general elections in Nigeria. Through a descriptive-statistical analysis of official election results released by the Independent National Electoral Commission and a critical review and analysis of extant secondary data which includes relevant journal articles, books, reports of Civil Society Organisations and Election Observer Missions on the general elections, it is found that voting pattern in the 2019 general elections in Nigeria was largely determined by psychological factors such as ethnic considerations and party affiliation rather than by personal qualities of candidates and performance of the party in government. The paper concluded that though voting based on ethnicity or party affiliation is not necessarily irrational or harmful at least from the perception of an informed voter, there is the need to sensitise the electorate on the need to encourage voting based on accomplishments of candidates and performance of the party in government.